2014
DOI: 10.1007/s10597-014-9776-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Barriers to Treatment Engagement: Adolescent Perspectives from the National Comorbidity Survey-Adolescent Supplement (NCS-A)

Abstract: The objective of this study was to assess youth self-reported treatment barriers in the past 12 months to obtain youth's perspective on reasons they seek treatment, do not engage in treatment, or terminate treatment. The present study uses data from the National Comorbidity Survey-Adolescent Supplement (NCS-A), a nationally representative survey administered to youth ages 13-18 that was conducted between February 1, 2001 and January 30, 2004. A total of 10,123 youth participated in the NCS-A study and provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
1
28
1
Order By: Relevance
“…Adolescents with substance use disorders and misuse are also less likely to access mental health services (Merikangas et al, 2011), and endorse more negative attitudes about seeking professional help (Gould et al, 2004). Not seeking treatment is associated with wanting to handle problems on one's own (Sylwestrzak et al, 2015), which is itself associated with more severe suicidal ideation and depression in adolescents (Labouliere et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with substance use disorders and misuse are also less likely to access mental health services (Merikangas et al, 2011), and endorse more negative attitudes about seeking professional help (Gould et al, 2004). Not seeking treatment is associated with wanting to handle problems on one's own (Sylwestrzak et al, 2015), which is itself associated with more severe suicidal ideation and depression in adolescents (Labouliere et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Young people's broader perceptions of help-seeking were reported as barriers in 39% of studies, and as facilitators in 4%. This subtheme captured young people's general attitudes towards mental health and help-seeking [31,49,53,55,59], help-seeking expectations [20,27,31,33,37,38,46,48,54,59,68,75] and perceptions about how help-seeking reflects on their character, such as perceiving help-seeking as a sign of weakness [21,49,54,60,63,73,75]. The latter was reported in all studies that included male-only samples.…”
Section: Young People's Individual Factorsmentioning
confidence: 99%
“…This subtheme only captured barriers and was more frequently reported in the quantitative studies than qualitative studies. Young people also reported past experiences to be both facilitators [26,40,47,53,73,74] and barriers [35,40,46,53] to seeking professional help for their mental health problems. Past positive experience was the most commonly reported facilitator, reported in 15% of studies.…”
Section: Young People's Individual Factorsmentioning
confidence: 99%
“…Children of parents treated for their mental disorders may profit from more accepting and less stigmatizing parental attitudes toward mental health treatment . Moreover, children of parents with mental disorders may be less likely to believe the problem would spontaneously remit or they can solve it on their own; both beliefs have been found to represent frequent barriers to help‐seeking . Third, the estimated association between maternal mental disorders and adolescent mental health service use may be mediated by child disorder severity .…”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, children of parents with mental disorders may be less likely to believe the problem would spontaneously remit or they can solve it on their own; both beliefs have been found to represent frequent barriers to help-seeking. 43 Third, the estimated association between maternal mental disorders and adolescent mental health service use may be mediated by child disorder severity. 19 Previous studies reported that children of parents with mental disorders developed more severe mental disorders, as Notes: All analyses were run in completer subsamples, based on the main sample of mother-adolescent dyads (N = 2939), and were restricted to those participants who reported any lifetime service use per sector (see Table 2).…”
Section: Stalujanis Et Almentioning
confidence: 99%